Transdiagnostic Tailored Internet- and Mobile-Based Guided Treatment for Major Depressive Disorder and Comorbid Anxiety: Study Protocol of a Randomized Controlled Trial - Weisel, Kiona K.; Zarski, Anna-Carlotta; Berger, Thomas; Schaub, Michael P.; Krieger, Tobias; Moser, Christian T.; Berking, Matthias; Ebert, David D. (Frontiers in Psychiatry, 2018)
Abstract Introduction: Depression is highly prevalent and often accompanied by comorbid anxiety disorder. Internet-based interventions have shown to be one effective treatment modality; however, comorbidities are often not targeted. Transdiagnostic tailored internet- and mobile-based interventions (IMIs) might be promising to overcome such issues. Aim: This study aims to evaluate the efficacy, moderators and cost-effectiveness of a transdiagnostic tailored internet- and mobile-based guided intervention for depression and comorbid anxiety in individuals with major depressive disorder (MDD). Method: Two-hundred participants with MDD will be randomly assigned to an eight-week guided self-help internet intervention (IC) or a six-month wait-list control group (WLC). Participants of the IC will receive weekly content-focused feedback on module completion as well as monitored adherence reminders from an eCoach. The primary outcome is clinician-rated depression severity (QIDS-C) at post-assessment assessed by diagnostic raters blind to study condition. Secondary outcomes include, e.g. change in diagnostic status (MDD and anxiety disorders), remission and response rates, disorder symptom severity, health related quality of life, incongruence related to needs and values, and behavioral activation. Assessments will take place at baseline (T1), post-assessment (T2), six-month follow-up (T3), and twelve-month follow-up in the IC. Data will be analyzed on an intention-to-treat basis and per protocol. A large number of a priori defined moderators of treatment outcome will be assessed at baseline and tested in predicting treatment outcome. Cost-effectiveness will be evaluated from a societal perspective. Discussion: The present study will provide evidence on the efficacy, potential cost-effectiveness, and moderators of a transdiagnostic tailored guided internet- and mobile-based treatment protocol. Trial registration: German Register of Clinical Studies DRKS00011690 (https://www.drks.de/drks_web/).